Geogebra Classroom For Overcoming Epistemological Obstacles And Enhancing Mathematical Literacy: A Bruner Perspective Theory - Raisatunnisa; Didi Suryadi; Siti Fatimah; Nanang Priatna; Jihe Chen; Agung Wicaksono (Koordinat Jurnal MIPA, 2026)
This study investigates how GeoGebra Classroom supports students in overcoming epistemological obstacles and enhancing mathematical literacy in learning exponents through Bruner’s representational approach. This qualitative phenomenological study involved 30 eighth-grade students from a junior high school in Gowa Regency, South Sulawesi, with 12 students purposively selected for learning sessions using GeoGebra Classroom. Three students representing low, medium, and high mathematical abilities were interviewed in depth. The research instruments included observation sheets, interview guides, and documentation of student learning activities. Data were collected through participatory observation, semi-structured interviews, and document analysis, and were analyzed using thematic analysis techniques. The study explored students’ learning processes through enactive, iconic, and symbolic stages. The findings indicate that GeoGebra Classroom facilitates gradual and exploratory learning through concrete manipulation and visual representations, enabling students to develop a deeper understanding of exponent concepts. However, some students experienced difficulties when transitioning to symbolic representations. This study contributes to digital mathematics education by proposing an instructional model that integrates technological tools with representational learning theory to enhance conceptual understanding and strengthen students’ mathematical literacy.